Myths of work the stereotypes and assumptions holding your organization back - Furnham, Adrian (London Kogan Page, 2018)
Buying a table tennis table will make your staff happier. Working eight hours a day, five days a week, will result in the most productivity. Paying higher salaries will always result in higher motivation. But will it really?
Includes index.
Keywords: Management